Perancangan Poros, Pulley dan V-belt pada Sepeda Motor Honda Beat FI 2014 - Prasojo Yogatama; Kardiman Kardiman; Rizal Hanifi (Peneliti.net, 2022)
Currently, many automotive vehicles have become the primary need for a company or individual. So that the supporting factors that can improve the vehicle must be prepared and already in a condition that is ready for use. To be able to work the vehicle, one that can support the running of the vehicle is the axle on the CVT (Continously Variable Transmission). This shaft serves to continue the rotation of the crankshaft to the Primary Pulley then the rotation is forwarded to the Secondary Pulley which is connected using a V-belt. Thus the condition of the shaft to be used must be in a state that is ready for use. So that there is a shortage or defect in the shaft, there will be a condition of the shaft both in terms of material and size and must be in a condition that is ready to be used. If replacement with a perfect shaft. For this reason, in making the shaft, it must really use calculations with high accuracy. This research has a problem formulation, namely how the working principle and function of a shaft in the engine element and how to calculate the shaft in the engine element. And aims to determine the working principle and function of a shaft in machine elements. From the results of observations and calculations that have been made, the design power is 8.58kW, the torque moment is 39.41Nm, the shaft diameter is 15.8mm, the diameter of the drive pully (ds1) is 115mm, the diameter of the drive pully (ds2) is 122mm, the speed of the V-belt is 10 ,2m/s, V-belt length 972.48mm, V-belt tension requirement 156.8N